Screening of pigeonpea (Cajanus cajan) mini-core germplasm sub-set for tolerance to wilt and pod borers - MURALI-BASKARAN, RAMASAMY KANAGARAJ; JAIN, SANJAY KUMAR; KAUSHAL, PANKAJ (The Indian Journal of Agricultural Sciences, 2022)
Biotic stresses are the major production constraints of pigeonpea crop including legume pod borer, spotted pod borer and pod fly and Fusarium wilt which cause significant yield losses. A mini-core sub-set of pigeonpea consisting of 146 accessions along with 4 control entries were screened against pod borer complex and wilt under field conditions in 2018 and 2019 at the research farm of ICAR of National Institute of Biotic Stress Management, Raipur, Chhattisgarh. Three accessions, viz. ICP7314, ICP7426 and ICP14819 were found to be moderately resistant to pod fly. Additionally, ICP 7426 was moderately susceptible to both the Lepidoptera pod borers. Five accessions, ICP9045, ICP9414, ICP9750, ICP14900 and ICP14903 were resistant to Fusarium wilt and 9 more accessions were moderately resistant. The identified accessions can be utilized in crop improvement which may provide resistance and/or tolerance against pod borers and wilt disease.